2019
DOI: 10.1177/2333794x19851390
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Latina Mothers of Children and Youth With Special Health Care Needs: A Qualitative Study

Abstract: Children and youth with special health care needs (CYSHCN) comprise a growing proportion of the pediatric population; the patient- and family-centered medical home provides a comprehensive model for caring for these patients. Given the limited literature available as well as extreme patient vulnerability, we sought to understand the experience of Latino parents in caring for their CYSHCN within our patient-centered medical home in an urban neighborhood in North Philadelphia. A convenience sample of 14 mothers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…74 Understanding experiences and needs of vulnerable families experiencing challenges with social determinants of health, including low income and LEP, is necessary to ensure quality and culturally effective care within a medical home. 34,37-39,51,75 Additional research is needed to identify the most effective training techniques for CWT caregivers with LEP including effective provision of translation services. 35 Video interpretation 55 and telehealth 58 may be useful tools for in-hospital training and addressing postdischarge needs of families of CWT with LEP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…74 Understanding experiences and needs of vulnerable families experiencing challenges with social determinants of health, including low income and LEP, is necessary to ensure quality and culturally effective care within a medical home. 34,37-39,51,75 Additional research is needed to identify the most effective training techniques for CWT caregivers with LEP including effective provision of translation services. 35 Video interpretation 55 and telehealth 58 may be useful tools for in-hospital training and addressing postdischarge needs of families of CWT with LEP.…”
Section: Discussionmentioning
confidence: 99%
“…3,19,35 Studies addressing needs and experiences of caregivers of CMC, especially CWT, from vulnerable populations including those with LEP are limited but support the medical home approach. 34,[36][37][38][39] An integrated patient-and family-centered medical home is essential for CWT living at home. This study aims to better understand the needs of caregivers of CWT living at home in an urban setting, foster their care and engagement in a medical home model, and inform the development of a family-centered simulation-based training curriculum.…”
mentioning
confidence: 99%
“…In terms of the access of these children, youth, and families to health services, this study's findings reveal they face difficulties because of the distance of the services and the slowness in which health problems are resolved. Other studies 13,24 conducted with health workers also report difficulties faced by the parents of children and youth with special healthcare needs because of the distance of their homes from the health units, a lack of adapted transportation, and the unit's improper infrastructure to receive this population. Note that these factors may directly interfere with which health services families seek.…”
Section: /13mentioning
confidence: 99%
“…Additionally, they concluded that the ordeal up to establishing a diagnosis also reveals barriers to the access of this population to health services. 17,24 These situations need to be discussed because PHC is the health system's entrance door, the guiding and coordinating basis of the Health Care Network (RAS). Hence, workers in these services should be prepared to meet this demand and prevent many avoidable hospitalizations.…”
Section: /13mentioning
confidence: 99%
“…In the United States, parents of children with chronic health conditions are more likely to be racial and ethnic minorities than caregivers of adults, with Latinos representing the largest minority group [12]. Nonetheless, Latinos and parents from other historically marginalized groups are underrepresented in studies of interventions that aim to support parents of children with chronic conditions [5,13]. Most published studies that explore the use of technology to enable the delivery of supportive interventions for parents of children with chronic conditions were from Europe [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%